(3GdHGOjGJ GdYjfjI aj GdfGOQGJ GdZjHjIs - (3YHO GdbGOQ Hf CHj UGdM Hf YHO Gddg GdLjdGfj, CHh eMeO,J (B561 (3g` s
(3ChdgG (B:s
(3aDGO Hg TeS GdeMHI SGWY hdjS dfLe GdYRd ajg ehGbY s
(3BNQgG (B:s
(3EfJgJ GdbUjOI GdoeHGQcI GdehSheI HGdHGOjGJ GdYjfjI aj GdfGOQGJ GdZjHjI s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3fXe s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(D 310) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs